Corporate Social Responsibility: Aktualisasi Ajaran Ihsan dalam Bisnis - Djakfar, Muhammad (ULUL ALBAB Jurnal Studi Islam, 2010)
Corporate is a business institution which has rapid development in the modern era. It is to fulfill the diverse society’s needs. In fact, corporation must be close to the society as both of them are interconnected and mutually demanding. To make them close, nowadays, it has been developed Corporate Social Responsibility, specifically, big sale corporate. With this program, corporate can help society based on their needs. Based on theological point of view, if it done wisely for God’s blessing, it is absolutely the actualization of Islamic teaching, Ihsan, in business context. Through the actualization of Ihsan, the business practitioners will be close not only both to others but also to God. According to Islamic teaching, there are many ways to earn fund for this program such as zakat, infak, sedekah, ang wakaf wich can be earned form Islamic employees. With this collected funding, corporate can invest in prospective business. And the result, then can be used as fund to succeed Corporate Social Responsibility program as well as to help the have not people. This program will be truly kindness program which importantly develop as the representation of Islamic teaching.